Los delitos y las penas : la ciudad judicial y penitenciaria: Alcalá de Henares, 1800-1900 / Gutmaro Gómez Bravo - Gómez Bravo, Gutmaro (Alcalá ensayo ; 24)
Premio Ciudad del Alcalá 2005 | Bibliografía: p. 261-280